Dogeaters - Hagedorn, Jessica Tarahata 1949- (New York Penguin Books, 1991)
The destinies of a varied group of characters--movie stars, department store clerks, the wealthiest man in the Philippines--are intertwined with a beauty pageant, a film festival, and an assassination, in a study of the Philippines under Marcos.
First published in the United States of America by Pantheon Books, 1990.
Fi-8711g donated by Dr. Ma. Teresa Sicat, Professor, Department of English & Comparative Literature, College of Arts and Letters, UP DIliman..
Keywords: Philippine fiction (English).